2022
DOI: 10.1002/joc.7641
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and multimodel projection of seasonal precipitation extremes over central Asia based on CMIP6 simulations

Abstract: Central Asia faces an increasing challenge related to water resources arising from severe droughts and floods that have impacted the region in the past decades. Using a comprehensive set of extreme precipitation indices, we assess the performance of CMIP6 models in representing observed precipitation extremes and investigate future responses of these extremes to greenhouse gas emissions under four shared socioeconomic pathways (SSP). Particularly, this study identifies robust signals of projected changes in sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…Zhang and Wang [39] reported that extreme precipitation in CA is expected to increase approximately linearly with increasing global warming. It has also been projected that seasonal extreme precipitation in southern CA follows an opposite trend than that in northern CA [40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang and Wang [39] reported that extreme precipitation in CA is expected to increase approximately linearly with increasing global warming. It has also been projected that seasonal extreme precipitation in southern CA follows an opposite trend than that in northern CA [40].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that GPCC is the most accurate in the global gridded precipitation dataset for average and extreme precipitation in Central Asia, outperforming other precipitation products on both the daily and annual scales [41][42][43][44]. As a result, it is widely used for precipitation and extreme precipitation studies in Central Asia [39,40,45]. The structure of this paper is as follows: The second section introduces the reference dataset and the CMIP6 models dataset used in this paper as well as the research methods.…”
Section: Introductionmentioning
confidence: 99%
“…Dike et al 17 evaluated seasonal precipitation extremes using CMIP6 and reported an increase in the severity of projected dry spells over Central Asia. Collazo et al 18 considered CMIP6 models' ability to represent observed extreme temperatures and concluded that the chosen models could not simulate cold days trends.…”
Section: Introductionmentioning
confidence: 99%
“…In response to the uncertainty of CMIP6 single mode estimation, this study applies the Multi-Model Ensemble (MME) to eliminate the influence of the "unicity" and "uncertainty" of CMIP6 single model prediction. MME is a method that utilizes the results of multiple model simulation and further ensemble average to reduce the uncertainty of model simulation, which is widely used in model simulation [32,33]. Therefore, this paper uses CMIP6 precipitation data averaged by Multi-Model Ensemble to predict the development trend of future extreme precipitation events in the Lancang-Mekong Basin.…”
Section: Uncertainty and Probability Distribution Methodsmentioning
confidence: 99%